Take the leap - Rachel Stark (Journal of New Librarianship, 2018)
Librarians who have worked in various types of libraries possess unique and valuable skills as a result of their experiences. Librarians should therefore be encouraged to apply to positions regardless of previous experience in a specific type of library, as their diversity of skills will benefit the communities they serve.